Binding of NAD(+)-Glycohydrolase to Streptolysin O Stabilizes Both Toxins and Promotes Virulence of Group A Streptococcus - Velarde, Jorge J. (mBio, 2017)
The globally dominant, invasive M1T1 strain of group A Streptococcus (GAS) harbors polymorphisms in the promoter region of an operon that contains the genes encoding streptolysin O (SLO) and NAD(+)-glycohydrolase (NADase), resulting in high-level expression of these toxins. While both toxins have been shown experimentally to contribute to pathogenesis, many GAS isolates lack detectable NADase activity. DNA sequencing of such strains has revealed that reduced or absent enzymatic activity can be associated with a variety of point mutations in nga, the gene encoding NADase; a commonly observed polymorphism associated with near-complete abrogation of activity is a substitution of aspartic acid for glycine at position 330 (G330D). However, nga has not been observed to contain early termination codons or mutations that would result in a truncated protein, even when the gene product contains missense mutations that abrogate enzymatic activity. It has been suggested that NADase that lacks NAD-glycohydrolase activity retains an as-yet-unidentified inherent cytotoxicity to mammalian cells and thus is still a potent virulence factor. We now show that expression of NADase, either enzymatically active or inactive, augments SLO-mediated toxicity for keratinocytes. In culture supernatants, SLO and NADase are mutually interdependent for protein stability. We demonstrate that the two proteins interact in solution and that both the translocation domain and catalytic domain of NADase are required for maximal binding between the two toxins. We conclude that binding of NADase to SLO stabilizes both toxins, thereby enhancing GAS virulence.